Cultural Aspect in Technology and Innovation Policy for Small and Medium Enterprises in Creative Industry: Agenda for Future Research - Gunawan, Arien Arianti; Aloina, Grace; Anggahegari, Prameshwara (STI Policy and Management Journal, 2024)
Technology and innovation are increasingly becoming the key elements for small and medium enterprises (SMEs) to achieve sustainable growth. However, policies related to technology and innovation in SMEs are rarely found which might be due to the limited access to financial support and organizational capability. In the case of creative industry, where cultural aspect plays an important role in some sectors, technology and innovation are often a contradiction with the cultural value. This study aims to explore the current discussion on technology and innovation policy between 2015 – 2024 in the Scopus database and provide an agenda for future research. The 15 articles selected mainly focus on SMEs in emerging countries that take culture into consideration. The study used a systematic literature review (SLR) and the articles are descriptively analyzed based on publication year, source title, subject area, and research methods. The articles are categorized into four themes namely technology, culture, innovation, and sustainability. The result shows that none of the relevant articles included in this study discussed cultural value in their technology and innovation policy recommendations. Future research directions are given and discussed, guiding researchers toward the most pressing and impactful aspects of the investigation.